Electronically reconfigurable filtenna for cognitive radios. Issue 2 (22nd December 2016) - Nachouane, Hamza; Najid, Abdellah; Riouch, Fatima; Tribak, Abdelwahed
ABSTRACT: A frequency tunable and bandwidth reconfigurable antenna with ring slot resonators embedded into its ground plane is presented. To achieve the bandwidth reconfigurability, two PIN diodes are inserted to couple or decouple two pairs of ring slot resonators from the antenna feed line. By switching the diodes on or off, the antenna can operate either in a wideband or narrowband mode. In the narrowband mode, two varactors are used to continuously tune the antenna operating frequency from 2.55 to 3.2 GHz. Due to the achieved bandwidths, the proposed structure can cover various bands used for LTE (1/2/7/33‐41 bands), WiMAX, and WLAN (802.11 b/g/n/s bands) applications. Similar radiation patterns with low cross‐polarization levels are obtained for different diodes states. The measured results show that the proposed design is potentially suitable for cognitive radio applications; in which the wideband mode is used for spectrum sensing while the narrowband mode for communicating over the selected channels. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:399–404, 2017